Kemandirian Belajar sebagai Faktor Penentu Hasil Belajar Peserta Didik Madrasah Tsanawiyah Sederajat - Didit Darmawan; Abdullah Hilmi (Student Research Journal, 2026)
In the post-pandemic period, the learning process at the Madrasah Tsanawiyah level continues to face significant challenges, particularly the emergence of disparities in student learning outcomes in general subjects. Many students have not yet fully returned to an active and focused learning pattern, resulting in uneven learning outcomes. Under these circumstances, self-directed learning has become an increasingly prominent aspect, as it relates to students’ ability to manage their own learning process without relying too heavily on teacher guidance. This study aims to examine how learning autonomy influences MTs students’ learning outcomes by reviewing existing studies. The research employs a literature review method using a qualitative descriptive approach, drawing on scientific sources from the past five years. The data were analyzed through content analysis to identify patterns of relationships emerging from previous studies. The results of the study indicate that learning autonomy tends to have a positive correlation with improved learning outcomes, although the magnitude of the effect is not always consistent across every study. Students who are better able to manage their own learning steps generally appear more active, more focused in their studies, and more aware of the processes they are undergoing. Nevertheless, the development of learning autonomy does not occur in isolation, as it remains influenced by the school’s learning environment and the way teachers manage instruction. Thus, it is clear that fostering independent learning is a key factor in efforts to improve student learning outcomes in the post-pandemic era.